On the transformation of muscle fibers in the process of sports training (literature review) - Myakotnykh, V. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The success of the training process is largely determined by the efficiency of building muscle composition, optimal for a particular sport. The review deals with the current understanding of the phenomenology and mechanisms of transformation of muscle fibers in the process of sports training, including the restructuring of energy systems and muscle contraction. Significant plasticity of skeletal muscle and muscle contraction enzymes in response to changes in functional requirements is shown. Some molecular mechanisms of regulation of energy metabolism gene expression and protein biosynthesis in mitochondria are revealed. The basic directions of the restructuring of the muscular compositions to be achieved in the training process.